If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5.7 + -5x + -5.9 + -1x = -5x + -6.3 Reorder the terms: -5.7 + -5.9 + -5x + -1x = -5x + -6.3 Combine like terms: -5.7 + -5.9 = -11.6 -11.6 + -5x + -1x = -5x + -6.3 Combine like terms: -5x + -1x = -6x -11.6 + -6x = -5x + -6.3 Reorder the terms: -11.6 + -6x = -6.3 + -5x Solving -11.6 + -6x = -6.3 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -11.6 + -6x + 5x = -6.3 + -5x + 5x Combine like terms: -6x + 5x = -1x -11.6 + -1x = -6.3 + -5x + 5x Combine like terms: -5x + 5x = 0 -11.6 + -1x = -6.3 + 0 -11.6 + -1x = -6.3 Add '11.6' to each side of the equation. -11.6 + 11.6 + -1x = -6.3 + 11.6 Combine like terms: -11.6 + 11.6 = 0.0 0.0 + -1x = -6.3 + 11.6 -1x = -6.3 + 11.6 Combine like terms: -6.3 + 11.6 = 5.3 -1x = 5.3 Divide each side by '-1'. x = -5.3 Simplifying x = -5.3
| y=5/9(F-32) | | (1)/(3)+(2)/(3)=(2)/(3)m-(2)/(3) | | (1)/(3)(x-9)=3x-2(x-1)+(5)/(3) | | 7x+2x+50=140 | | 27,3/0,7 | | (1)/(3)(5x+3)-(1)/(4)(x+5)=4 | | (1)/(3)(21-3a)=6-1 | | x^2-3-10=0 | | (1)/(2x)+(6x-9)/(3x)=(2)/(x) | | (1)/(2)x+7=9 | | (1)/(2)a=7 | | (1)/(2)-(3m)/(4)+7=4m-9-(m)/(28) | | (1)/(2)+4n=3n-(3)/(2) | | (1)/(2)+(3)/(8)y=(5)/(12)+(5)/(8)y | | (1)/(2)(6x-10)+x=15 | | (9x^2)-5x-3=0 | | (-x^2)-12x-36=0 | | (1)/(2)(3x+2)-(1)/(5)(x+6)=5 | | (1)/(15)+(1)/(5x)=(2)/(3x) | | (1)/(0.03-x)=0 | | -32a-1=-30a | | (0.84-x)/(0.96+x)=0.203 | | (0.8-2x)/(0.2+x)=2.5 | | (0.6x+19)/x=0.2x | | (0.6x+19)/x=0.2 | | (0.5y+4)/(1.2y+8)=5/3 | | 3x-8+2x+-4-x=48 | | 4+5+X+X=28 | | (0.5x/21)+(0.5x/24)=10 | | (0.5x-10)/(x-4)=(0.5x+2)/(2x-8) | | x+X+X+X+4+5=28 | | 17=x+12 |